Effectiveness and Efficiency of E-learning among Students of Higher Education during the COVID-19 Pandemic: A Comparative Study of Malaysia and India - Abhijit Das; Miguel Córdova Espinoza; Che Ming; Kok Ban Teoh; Gim Seng Lee; Akash Jagdale; Rajesh Kumar Nair; Yashaswini. V; Padmalini Singh; Anurag Malik (International Journal of Tourism and Hospitality in Asia Pasific, 2021)
The worldwide educational system was greatly damaged by COVID-19 pandemic and the urge in closing of educational institutions had affected children around the world. The infectious character of COVID-19 had signaled those teachers and students’ personal interactions were greatly influenced by confinement and forced isolation. As the consequence, educations have fundamentally been shifted significantly towards E-learning, which involves teaching on interactive networks and long–distance. E-learning is the only way for students to continue their study in their house during the pandemic. The study aims to determine the effectiveness and efficiency of various modes, devices, methods of E-learning platforms. The primary data from national and international institutions obtained through a survey with the community from different schools, colleges, and universities, to determine the effectiveness and efficiency of E-learning for students. A total of 200 respondents from Malaysia and India have completed the online survey. The findings of the study indicated that the efficiency and effectiveness of E-learning in Malaysia is higher than in India. Students prefer E-learning in future due to its wide acceptance among the community. The findings provide some new insights that will contribute towards E-learning in both countries.